2018
DOI: 10.14207/ejsd.2018.v7n3p287-300
|View full text |Cite
|
Sign up to set email alerts
|

Visual Landscape Quality Assessment in Historical Cultural Landscape Areas

Abstract: Various factors such as rapid population increase, socio-economic changes and uncontrolled urbanization observed in cities caused many changes in urban areas. These changes damage natural and cultural landscape areas. It is observed that especially historical landscape areas couldn"t be protected as well as planning and management of these areas couldn"t be provided. Accordingly, constitution of inventory studies oriented natural, cultural and historical sources; presentation of planning and management decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The selection of appropriate evaluation criteria is essential in such studies. Keleş E., Atik D. and Bayrak G. [42] stated that visual quality assessment is based on 14 parameters (coherence, imageability, historicity, sense of place, visual impressiveness, stewardship, complexity, legibility, originality, accessibility, naturalness, security, inconsistency and city identity), which they used to evaluate places with significant historical values. Alternatively, Myga-Piątek U.…”
Section: Evaluation Of the Landscape In Existing Studiesmentioning
confidence: 99%
“…The selection of appropriate evaluation criteria is essential in such studies. Keleş E., Atik D. and Bayrak G. [42] stated that visual quality assessment is based on 14 parameters (coherence, imageability, historicity, sense of place, visual impressiveness, stewardship, complexity, legibility, originality, accessibility, naturalness, security, inconsistency and city identity), which they used to evaluate places with significant historical values. Alternatively, Myga-Piątek U.…”
Section: Evaluation Of the Landscape In Existing Studiesmentioning
confidence: 99%
“…Local residents are therefore concerned about environmental and cultural changes that accompany tourism development [21,22], which are first experienced via visual impacts [23]. Keleş et al has emphasized that understanding visual landscape changes can help identify areas in need of protection within the framework of cultural heritage conservation planning, as well as address lost natural and cultural characteristics, physical development, and village social life [24]. Further, research has demonstrated that the quality of the visual landscape directly affects residents' mental health and well-being [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers and urban designers have long held the view as a basic proposition that urban form or urban spatial configuration influences human perception of urban space, especially visual perception (M. L. Benedikt, 1979; Keles et al, 2018; Llobera, 2003). Previous studies indicated that it is crucial to evaluate the potential visual impacts of existing and proposed urban forms before making new urban construction decisions (Hernández, Garcia, & Ayuga, 2004; Yin and Shiode, 2014).…”
Section: Introductionmentioning
confidence: 99%